PENGENDALIAN LAMPU DISCO LED MENGGUNAKAN APLIKASI BERBASIS ARDUINO - Maulana Rohmatullah Al Mahmudi Shabet; Nur Khafidhoh (Jurnal Komunikasi, 2023)
The people of East Java are generally very familiar with Ketoprak. Especially in the Situbondo area, it seems as if Ketoprak is one of the people's lives and beats other arts such as Srandul, Emprak and other folk arts. Current technological developments encourage people to continue to think creatively, but also maximize the performance of existing technologies to ease human work in everyday life such as home lighting control devices combined with microcontroller components and utilizing Bluetooth facilities available in the android application (Kharimun Tholib). ,2019). Therefore, if all the lights in a stage such as the cultural arts of Ketoprak Sinar Pemuda are controlled without having to turn on the switch, then the role of the microcontroller, Android application and Bluetooth device is to provide comfort and convenience, especially for teenagers and parents in controlling led disco lights. Communication between the Android application and the microcontroller can be done wirelessly using Bluetooth, where the Bluetooth module in the Android application and the microcontroller system can communicate using serial data. The introduction of bluetooth on the Android application can be used to control lights using a cellphone. This is done by initializing the bluetooth module in the form of a string to a character code that has been recognized by the microcontroller. If the cellphone is out of range of the bluetooth wireless module of the bluetooth module, the Led disco light control will not work because the bluetooth connection will be automatically disconnected